Тенденції розвитку полікультурної освіти студентів університетів у Федеративній республіці Німеччина - Кривко, Марина Юріївна; Kryvko, M. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Дослідження присвячено проблемі визначення тенденцій розвитку полікультурної освіти студентів університетів у Федеративній республіці Німеччина. У дисертації розкрито ґенезу полікультурної освіти в Німеччині. Виокремлено три етапи розвитку полікультурної освіти в Німеччині: І етап – 1871-1945 рр.; ІІ етап – 1945-1990 рр., ІІІ етап – 1990 – по теперішній час, наведено характеристику кожного з них.

The research is devoted to the issue of identifying trends in the development of multicultural education of university students in the Federal Republic of Germany. The dissertation reveals the genesis of multicultural education in Germany. Three stages of the development of multicultural education in Germany are distinguished: Stage I – 1871–1945; Stage II – 1945–1990; Stage III – 1990 to the present, with a characterization of each stage provided.
Trends in the development of multicultural education of students in the Federal Republic of Germany
Науковий керівник : Ткачова Наталія Олександрівна, доктор педагогічних наук, професор
Keywords: SOCIAL SCIENCES::Social sciences::Education; полікультурна освіта; Федеративна республіка Німеччина; студенти; формальна освіта; неформальна освіти; система освіти; освітній процес; Європейський союз; компетентність; multicultural education; Federal Republic of Germany; students; formal education; non-formal education; education system; educational process; European Union; competence